The food expenditure in Poland and other European Union countries – a comparative analysis - Maciejewski, Grzegorz (Olsztyn Economic Journal, 2019)
The purpose of this paper is to present the results and conclusions of a comparative analysis of Poland and other European Union countries regarding the level of food expenditure, the share of food expenditure in the structure of total expenditure and the direction of changes in these areas that took place in the years 2006-2016. The conducted analysis employed the desk research method using logical inference methods, based on Eurostat data and academic literature. For a more detailed analysis of the research findings, a cluster analysis was carried out using one of the hierarchical methods – the Ward’s method. The obtained results of the analyses permitted the conclusion that disproportionate food consumption in the household sector between individual countries should still be considered as large – although the differentiation clearly decreased in the analysed period. The less developed countries from Central and Eastern Europe are still far from adopting the service consumption model that would allow for a more complete satisfaction of higher-ranking needs.